2020
DOI: 10.3389/fmicb.2020.00222
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Efficacy of Thermostable Biosurfactant in Heavy Metal Bioremediation and Surface Treatment in Vegetables

Abstract: Biosurfactants are amphiphilic molecules which showed application in the food, medical, and cosmetics industries and in bioremediation. In this study, a marine spongeassociated bacteria (MSI 54) was identified as a biosurfactant producer which showed high emulsification and surface tension-reducing property. The isolate MSI 54 was identified as Bacillus sp. and the biosurfactant was chemically characterized as a lipopeptide analog based on the spectral data including Fourier transform infrared spectroscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 45 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Validated results revealed that potential application of biosurfactants in mouthwash preparations is safe and a feasible alternative ( Farias et al, 2019 ). Biosurfactants are also applicable for the remediation of heavy metals from contaminated environments apart from hydrocarbon bioremediation ( Ravindran et al, 2020 ). Several researchers demonstrated application of biosurfactants such as rhamnolipid, lipopeptide, and glycoprotein in microbe-enhanced oil recovery ( Arora et al, 2019 ; Purwasena et al, 2019 ).…”
Section: Significance Of Polycyclic Aromatic Hydrocarbon Remediation mentioning
confidence: 99%
“…Validated results revealed that potential application of biosurfactants in mouthwash preparations is safe and a feasible alternative ( Farias et al, 2019 ). Biosurfactants are also applicable for the remediation of heavy metals from contaminated environments apart from hydrocarbon bioremediation ( Ravindran et al, 2020 ). Several researchers demonstrated application of biosurfactants such as rhamnolipid, lipopeptide, and glycoprotein in microbe-enhanced oil recovery ( Arora et al, 2019 ; Purwasena et al, 2019 ).…”
Section: Significance Of Polycyclic Aromatic Hydrocarbon Remediation mentioning
confidence: 99%
“…For example, it has been reported that at two-fold CMC, the biosurfactant produced by Bacillus sp . shows high heavy metal removal, mainly for Cd (99.93%), Pb (97.73%), Mn (89.5%), and Hg (75.5%) showing the formation of a co-precipitate [ 92 ]. Biosurfactant concentration has been reported to be an important parameter.…”
Section: Environmental Uses Of Biosurfactantsmentioning
confidence: 99%
“…The role of LPs in the removal of heavy metals from the environment has been widely reported [109] , [110] , [111] , [112] . Surfactin, synthesized by bacteria of the Bacillus genus, is capable of removing zinc and copper [103] , [113] ; Colistin, produced by Paenibacillus polymyxa , binds efficiently to copper [114] ; pseudofactin II, produced by Pseudomonas fluorescens BD5, also interacts with zinc and copper [109] ; while the MSI54 LP, produced by a Bacillus bacterium isolated from a marine sponge has an affinity for lead, mercury, manganese, and cadmium [115] . The ionic charge of LPs is known to play an important role in their interaction with heavy metals.…”
Section: Lipopeptide Relationships With Heavy Metalsmentioning
confidence: 99%